UPAYA MENINGKATKAN PENGETAHUAN KESEHATAN GIGI DAN MULUT MELALUI EDUKASI BAHAYA PENGGUNAAN â€œBEHEL FASHIONâ€ PADA MASYARAKAT MARGASARI - Suhartono, Budi; Hutami, Islamy Rahma; Mayangsari, Regilia Shinta; Yuniar, Savira Nurazky; Indrawati, Silvia Vera; Dimas P. P., Muhammad (Faculty of Dentistry Universitas Islam Sultan Agung, 2023)
Background: Today, many teenagers in Indonesia are using braces not as orthodontic appliances for the treatment of malocclusion but only as a â€˜fashionâ€™ . Dental treatment that carried out by incompetent operators can actually cause far greater dangers and losses. The impact that can occur due to the use of braces by dental technicians can arise from tooth decay, plaque accumulation, root resorption, bone resorption, inflammation of the supporting tissues of the teeth, to disorders of the temporomandibular joint. Method: The solution to the problem is carried out by educating the community, one of them are in Margasari, Tegal. Dental Health Education is carried out using poster media to make it more interactive, effective and efficient. Evaluation of the implementation is done by using a questionnaire. The results of the questionnaire were tabulated using SPSS with the Wilcoxon non-parametric test method. Result: wilcoxon signed rank shows that there are 0 negative ranks, 24 positive ranks, and 1 ties. Z value based on negative ranks are -4.322 Conclusion: There is an increase in knowledge of respondents after being given education.